2010
DOI: 10.1038/ejcn.2010.137
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and endothelial function: a battle between caffeine and antioxidants?

Abstract: Although coffee is largely consumed by adults in Western countries, controversy exists about its impact on the cardiovascular system. We recently demonstrated that caffeinated and decaffeinated espresso coffee have different acute effects on endothelial function in healthy subjects, measured using flow-mediated dilation (FMD) of the brachial artery. In this study, we measured the anti-oxidant capacity of two coffee substances in terms of free stable radical 2,2-diphenyl-1-picryl-hydrazyl 50% inhibition (I 50 D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 7 publications
3
18
0
6
Order By: Relevance
“…According to studies by Buscemi et al [26] and Shechter et al [27], the effect of caffeine (200 and 130 mg, respectively) on FMD is controversial. Accumulated evidence indicates caffeine intake (200 mg or more) increases blood glucose in humans [28,29].…”
Section: Discussionmentioning
confidence: 98%
“…According to studies by Buscemi et al [26] and Shechter et al [27], the effect of caffeine (200 and 130 mg, respectively) on FMD is controversial. Accumulated evidence indicates caffeine intake (200 mg or more) increases blood glucose in humans [28,29].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies suggested that its healthy effects in chronic diseases might depend on the antioxidant compounds contained in coffee, including vitamin E, niacin, potassium and magnesium [18]. The beneficial effects of coffee polyphenols in preventing chronic diseases could be due to their ability to improve endothelial function [40] and to suppress vascular endothelial cell expression of proinflammatory cytokines [41], with the consequent upregulation of adhesion molecules and monocyte adhesion [42]. It might also be due to the anti-inflammatory effects of coffee diterpenes [43,44], although these compounds are thought to be removed by coffee paper filters.…”
Section: Discussionmentioning
confidence: 98%
“…As between-study heterogeneity is commonly seen in metaanalyses [41], exploring the potential source(s) of heterogeneity is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The total antocyanin content was measured by using the spectrophotometric method as reported by Rapisarda et al (18); cyanidin 3-glucoside (Extrasynthese) was used as a standard to construct a calibration curve. The radical scavenging activity of blood orange juice was measured by using a spectrophotometric method and the free stable radical 2,2-diphenyl-1-picryl-hydrazyl according to the method proposed by Brand-Williams et al (19) with minor modifications as described elsewhere (20). The total content of the polyphenolic compound was measured by using the spectrophotometric method described by Asami et al (21); gallic acid (Fluka) was used as a standard to construct a calibration curve.…”
Section: Orange Juicementioning
confidence: 99%